An Analytical Study of the Da’wah Movement of Prophet Muhammad in Relation to Social Movement Theory - Aswar, Hasbi; Afifi , Subhan (Journal of Islamic Thought and Civilization, 2024)
This article explores the da’wah activities of Prophet Muhammad through the perspective of social movements to provide new insights. This article explains that the Prophet Muhammad was not only a religious activist who worked to spread Islam but also a statesman who successfully led his followers to establish a new state in Yathrib (Medina). This research focuses on the Prophet’s endeavours in political activism through the movement aimed at achieving social and political change. This study will analyse the da’wah movement using social movement perspectives, focusing on structural-functional theory, resource mobilization theory, political opportunity structure, and framing theory. This article argues that the success of the Prophet’s da’wah and political initiatives is rooted in the structural conditions of Mecca and the mobilization strategies. The strength of religious narratives and the capacity to exploit narrow political opportunities while generating the new ones have played a vital role to support da’wah activities. This research uses a historical qualitative methodology, leveraging primary and secondary sources to analyse the socio-political landscape of Mecca, the Prophet’s resource mobilization techniques, and the framing of his religious messages. This article is an initial investigation into the integration of social movement theories within the context of Islamic social movements, highlighting the importance of overcoming Western secular dominance of social movement studies.